استخدام الارتباط القانوني لدراسة أثر المُتغيرات الدِّيمُوغرافيَّة على بعض مؤشرات التنمية الاقتصادية في سورية خلال الفترة 2000-2010 - العلي إبراهيم; دريباتي يسيرة; أحمد وسيم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى دراسة أُثر المتغيرات الديموغرافيّة على مؤشرات التنمية الاقتصادية باستخدام الارتباط القانوني. فقد تم تحديد المتغيرات الديموغرافية (معدل النمو السكاني, معدل الوفيات الخام, معدل الخصوبة الكلي, معدل صافي الهجرة), وتم تحديد أهم متغيرات التنمية الاقتصادية (معدل نمو الناتج المحلي الاجمالي, معدل نمو الدخل القومي), وبعدها تم إجراء الحسابات اللازمة على هذه المتغيرات وكان من أهم النتائج التي تمّ التوصّل إليها: -يوجد نموذج ارتباط قانوني يعبّر عن العلاقة بين المتغيرات القانونيّة الديموغرافيّة, والمؤشرات التنموية ممثلة في الناتج المحلي الإجمالي والدخل القومي, وتبيّن أنّ معامل الارتباط القانوني بلغ 0.992 مما يدل على علاقة قويّة جدّاً. تتمثل أهم التوصيات في الآتي: - ضرورة الأخذ بعين الاعتبار أثناء إعداد الخطط التنمويّة الهادفة إلى زيادة الناتج المحلي الإجمالي والدخل القومي واتباع سياسة سكانية لتخفيض معدلات الولادة ومعدلات الوفاة ودعم الرعاية الصحيّة للسكان في جميع المناطق. - المحافظة على مستوى الخصوبة المنخفض في سورية وخاصة في السنوات الثلاثة الأخيرة للدراسة من خلال نشر الوعي بين الأمهات والتثقيف الجنسي, ونشر وسائل منع الحمل في إطار تدعيم الرعاية الصحية الأسرية على المستوى الكلي. This research aims to study the impact of demographic variables on the economic development indicators using canonical correlation. Have been identified demographic variables (population growth rate, crude death rate, total fertility rate, net migration rate), was to identify the most important economic development variables (GDP growth rate, national income growth rate), and then was making the necessary statutory accounts on this The variables of the most important results that have been reached: -canonical model expresses the relationship between the legal and demographic variables, and indicators of development represented by the gross domestic product and national income, shows that the legal correlation coefficient was 0.992, which indicates a very strong relationship. The main recommendations are as follows: - Need to take into account during the preparation aimed at increasing GDP and national income and follow the population policy to lower birth rates and death rates and health care support for people in all areas of development plans. - Maintain a low fertility level in Syria, particularly in the last three years of the study by raising awareness among mothers and sex education, and the dissemination of contraceptive methods in the context of strengthening family health care at the macro level.